Risk Management of University During Covid-19 Pandemic: A Look at Academic Support Unit - Anita Primaswari Widhiani; Retnaningsih (Business Review and Case Studies, 2022)
In the time of the pandemic, universities are changing the way of doing business. The aim of this research is to study how the academic support unit of a university adjusting to the condition and manage the risks that comes with the adjustment. Data collected by in-depth interview with unit head and her subordinates. The jobs with the biggest risks are providing diploma and final transcript and conducting graduation ceremony. Providing diploma and final transcript inherently carry legal and reputation risks and providing the paper version of those documents increase the probability of those risks. The first scenario is to mitigate every risk that may come by doing the job with pandemic protocols. The second scenario is to develop e-diploma system that mitigate the risks associated with producing and producing paper diploma. Conducting physical graduation ceremony during the pandemic requires arduous health and safety measures. The alternative is having digital graduation ceremony on virtual reality platform to mitigate the risks of conducting physical graduation ceremony while still maintaining a sense of engagement. The result of the research shows how universities, especially in academic support, can embrace the change while managing the risks that come with the change. Keywords: risk management, university, academic support unit, Covid-19, working at home